Educational Public Policies in Brazilian Public Municipal Schools of Full-Time Education (Interdisciplinary Studies Journal, 2024)
This article aims to understand the implementation of public educational policy for the full-time school regime, in elementary education in Brazilian municipal public networks. The study presents the phenomenological paradigm. Descriptive, bibliographic and documentary research uses public educational policies that include guidelines on Full-Time Comprehensive Education as data collection sources. Semi-structured interviews were carried out with school managers from 5 municipal schools. The information collected is interpreted according to pre-established analysis categories. The results involve an analysis and reflection on the implementation of Comprehensive Education in Public Schools in different educational contexts. Municipal full-time elementary schools develop pedagogical actions and strategies focused on organizing time and spaces; in curricular organization; in activities and work methodology; and, criteria for choosing participating students according to their reality and territory.
Keywords: Full-Time Education; Full-Time; Educational Public Policies